SPHERE: BIM Digital Twin Platform - Rubén Alonso; Mikel Borras; Rembrandt H. E. M. Koppelaar; Alessandro Lodigiani; Eduard Loscos; Emre Yöntem (Proceedings, 2019)
SPHERE (Service Platform to Host and sharE REsidential data) is a 4-year Horizon 2020 EU-funded project, carried out by 19 SMEs, RTOs and Large Enterprises across Europe. The platform aims to provide citizens, AEC stakeholders, as well as city administrations and urban developers, with an integrated ICT platform that will allow for a better assessment and development of the Design, Construction and Performance of residential buildings. SPHERE platform will facilitate improvements in the energy performance of buildings from the start of the construction process. In addition, it will also reduce time, costs, and the environmental impact of construction processes and improve the indoor environment due to a seamless integration of each meaning dimension and respective stakeholders within the platform.